2020
DOI: 10.3390/ijerph17072342
|View full text |Cite
|
Sign up to set email alerts
|

Daily Travel and Wellbeing among the Elderly

Abstract: The purpose of this Special Issue is to introduce and demonstrate the importance of daily travel in elderly people's lives. In doing so, we wish to present recent advances made in this emerging field. Our overall goal is to provide a broad understanding of the links between psychological wellbeing and travel, the importance of daily travel, and the different evaluations and measures used to assess the experience of daily travel and the quality of life of the elderly.There are several different reasons for focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Public transport use can also influence mental health and wellbeing among older people (Ettema et al, 2010;Friman et al, 2018;Friman & Olsson, 2020;McCarthy & Habib, 2018;Mokhtarian, 2019). First, public transport use can link to mental health by directly affecting older people's moods and feelings during travel.…”
Section: Public Transport Use and Healthmentioning
confidence: 99%
“…Public transport use can also influence mental health and wellbeing among older people (Ettema et al, 2010;Friman et al, 2018;Friman & Olsson, 2020;McCarthy & Habib, 2018;Mokhtarian, 2019). First, public transport use can link to mental health by directly affecting older people's moods and feelings during travel.…”
Section: Public Transport Use and Healthmentioning
confidence: 99%
“…These difficulties and barriers affect older adults’ ability to move around safely and independently and prevent them from maintaining social life as actively as they would like, which is often considered essential to maintaining social connectedness, independence, and a sense of well-being [ 8 , 9 ]. Thus, there is a need to provide accessible and affordable transportation options and support older adults in transportation planning and selecting the means of transport that best fit their needs and preferences [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recognition of the benefit of tourism on well-being elevates the demand of older adults for tourism when they tend to have more free time ( 34 ). Compared with the younger people, the old people are more actively involved in travel ( 35 ). Studies have suggested that active participation in tourism promotes the health condition and longevity of the older adult ( 36 ).…”
Section: Introductionmentioning
confidence: 99%